Chlorhexidine for facility-based umbilical cord care: EN-BIRTH multi-country validation study - Sojib Bin Zaman; Abu Bakkar Siddique; Harriet Ruysen; Ashish KC; Kimberly Peven; Shafiqul Ameen; Nishant Thakur; Qazi Sadeq-ur Rahman; Nahya Salim; Rejina Gurung; Tazeen Tahsina; Ahmed Ehsanur Rahman; et al. (BMC, 2021)
Abstract Background Umbilical cord hygiene prevents sepsis, a leading cause of neonatal mortality. The World Health Organization recommends 7.1% chlorhexidine digluconate (CHX) application to the umbilicus after home birth in high mortality contexts. In Bangladesh and Nepal, national policies recommend CHX use for all facility births. Population-based household surveys include optional questions on CHX use, but indicator validation studies are lacking. The Every Newborn Birth Indicators Research Tracking in Hospitals (EN-BIRTH) was an observational study assessing measurement validity for maternal and newborn indicators. This paper reports results regarding CHX. Methods The EN-BIRTH study (July 2017-July 2018) included three public hospitals in Bangladesh and Nepal where CHX cord application is routine. Clinical-observers collected tablet-based, time-stamped data regarding cord care during admission to labour and delivery wards as the gold standard to assess accuracy of women's report at exit survey, and of routine-register data. We calculated validity ratios and individual-level validation metrics; analysed coverage, quality and measurement gaps. We conducted qualitative interviews to assess barriers and enablers to routine register-recording. Results Umbilical cord care was observed for 12,379 live births. Observer-assessed CHX coverage was very high at 89.3-99.4% in all 3 hospitals, although slightly lower after caesarean births in Azimpur (86.8%), Bangladesh. Exit survey-reported coverage (0.4-45.9%) underestimated the observed coverage with substantial "don't know" responses (55.5-79.4%). Survey-reported validity ratios were all poor (0.01 to 0.38). Register-recorded coverage in the specific column in Bangladesh was underestimated by 0.2% in Kushtia but overestimated by 9.0% in Azimpur. Register-recorded validity ratios were good (0.9 to 1.1) in Bangladesh, and poor (0.8) in Nepal. The non-specific register column in Pokhara, Nepal substantially underestimated coverage (20.7%). Conclusions Exit survey-report highly underestimated observed CHX coverage in all three hospitals. Routine register-recorded coverage was closer to observer-assessed coverage than survey reports in all hospitals, including for caesarean births, and was more accurately captured in hospitals with a specific register column. Inclusion of CHX cord care into registers, and tallied into health management information system platforms, is justified in countries with national policies for facility-based use, but requires implementation research to assess register design and data flow within health information systems.